Social Reproduction, Gender, and Academia during the Covid-19 Pandemic: Experiences from Ecuador - Tapia-Tapia, Silvana; Fajardo-Monroy, Gabriela; Padrón-Palacios, Tatiana (Sociedad y Economía, 2023)
This article presents the findings of a study that employed qualitative and quantitative socio-legal methods to monitor the impact of the Covid-19 pandemic on the personal and professional lives of Ecuadorian women scientists in 2020. The objective was to evidence the intersection between gender inequality, socioeconomic inequity derived from unpaid work overload, and time poverty as a disruptive factor of integral well-being. As a conclusion, it was observed that the total workload increased, the spatiotemporal compartmentalization of life was diluted, and state and institutional responses to the crisis did not incorporate a gender approach to these problems. Women academics felt invisible, their quality of life decreased, and their risk of impoverishment and professional stagnation increased. It is recommended that social reproduction be recognized as a priority axis in institutional policies, especially in times of crisis.